Cyclooxygenase-2 inhibition for the prevention of subglottic stenosis - Cetin, Selma (2012)
OBJECTIVE: We aimed to evaluate the role of targeted cyclooxygenase-2 (COX-2) inhibition in reducing scarring associated with a subglottic airway mucosal injury. DESIGN: 34 New Zealand white rabbits underwent anterior cricothyroidotomy. Subglottic stenosis (SGS) was created by carbon dioxide (CO2) laser injury. INTERVENTION: Treatment consisted of intraperitoneal (IP) injection of celecoxib or vehicle for 4 days. Endoscopies were performed to assess injury and healing. Subglottic mucosal secretions were collected with Gelfoam swabs before and after injury and at subsequent time points. Animals were euthanized at 3 or 8 weeks after injury and airways were excised, followed by gross examination and histological analysis to assess the severity of SGS. Secretions were analyzed for interleukin-1β (IL-1β), prostaglandin E2 (PGE2) and matrix metalloproteinase-8 (MMP-8) by Enzyme-Linked Immunosorbent Assays (ELISAs). RESULTS: Endoscopy showed mild to moderate stenosis in the celecoxib-group, but mild to severe stenosis in the vehicle group. Histological assessment confirmed and quantified reduction in stenosis and scarring as well as advanced re-epithelialization. In the healing tissue, mucosal thickening (stenosis) was reduced significantly (p=0.02) in celecoxib-treated animals compared to vehicle, at 3 and 8 weeks (decrease in thickness by 32% and 49%, respectively). Collagen density (fibrosis) was also reduced 25% at both 3 and 8 weeks, but did not achieve statistical significance (p=0.195). Reduced level of PGE-2 in the subglottic mucosal secretions was correlated with mucosal thickness at 8 weeks (p=0.021). CONCLUSION: Short duration anti-inflammatory therapy resulted in reduced stenosis and fibrosis with correlation of PGE-2 levels in subglottic mucosal secretions.